THE EFFECT OF THE TEAM GAMES TOURNAMENT LEARNING MODEL ASSISTED BY ENGKLEK GAMES ON THE LEARNING OUTCOMES OF ELEMENTARY STUDENT OF CULTURAL HERITAGE MATERIALS - Agustina, Melda Dwi; Prasetyaningtyas, Fitria Dwi (STKIP Citra Bakti, 2026)
The low understanding of the fifth graders of cultural heritage materials is caused by the low interest, motivation, and literacy of students, which has an impact on learning outcomes. Therefore, the purpose of this study is to determine the influence of the Team Games Tournament learning model assisted by “Engklek Games” on the learning outcomes of the fifth graders on cultural heritage materials. This study uses a quasi-experimental research type and a Nonequivalent Control Group Design. The research population amounted to 59 students in the fifth grade including 32 students of SDN Langgenharjo 01 as an experimental class and 27 students of SDN Bakaran Kulon 03 as a control class. Total sampling was used for sampling in this study. Data collection techniques include learning outcome tests and student activity observation sheets, while data analysis uses normality tests, homogeneity tests, t-tests, and n-gain tests. The results of the study showed (sig. 0.000 < 0.05) that the application of the Team Games Tournament learning model assisted by “Engklek Games” had a significant effect on learning outcomes in cultural heritage materials. The average n-gain of the experimental class was 0.7392 > 0.5909 of the control class, which showed that the improvement of learning outcomes was more optimal in the experimental class. In addition, student learning activities are in the very active category. Based on the analysis carried out, the Team Games Tournament learning model assisted by “Engklek Games” has proven to be effective in improving student learning outcomes.